Simulation study of single event effects sensitivity on commercial power MOSFET with single heavy ion radiation - Erman Azwan Yahya; Ramani Kannan; Lini Lee (Institute of Advanced Engineering and Science, 2019)
High-frequency semiconductor devices are key components for advanced power electronic system that require fast switching speed. Power Metal Oxide Semiconductor Field Effect Transistor (MOSFET) is the most famous electronic device that are used in much power electronic system. However, the application such as space borne, military and communication system needs Power MOSFET to withstand in radiation environments. This is very challenging for the engineer to develop a device that continuously operated without changing its electrical behavior due to radiation. Therefore, the main objective of this study is to investigate the Single Event Effect (SEE) sensitivity by using Heavy Ion Radiation on the commercial Power MOSFET. A simulation study using Sentaurus Synopsys TCAD software for process simulation and device simulation was done. The simulation results reveal that single heavy ion radiation has affected the device structure and fluctuate the I-V characteristic of commercial Power MOSFET.